2006
DOI: 10.1038/ng1754
|View full text |Cite
|
Sign up to set email alerts
|

High mutation rates have driven extensive structural polymorphism among human Y chromosomes

Abstract: Although much structural polymorphism in the human genome has been catalogued, the kinetics of underlying change remain largely unexplored. Because human Y chromosomes are clonally inherited, it has been possible to capture their detailed relationships in a robust, worldwide genealogical tree. Examination of structural variation across this tree opens avenues for investigating rates of underlying mutations. We selected one Y chromosome from each of 47 branches of this tree and searched for large-scale variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
265
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(285 citation statements)
references
References 30 publications
14
265
0
1
Order By: Relevance
“…The distal end of the long arm of the Y chromosome is the heterochromatin region, one of the most variable in length in the human genome [28]. Increased length of the Y chromosome is heritable, and Yqh+ has not been associated with an abnormal phenotype [29].…”
Section: Discussionmentioning
confidence: 99%
“…The distal end of the long arm of the Y chromosome is the heterochromatin region, one of the most variable in length in the human genome [28]. Increased length of the Y chromosome is heritable, and Yqh+ has not been associated with an abnormal phenotype [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that gene conversion events of up to 9 kb have been reported on the Y chromosome (Hallast et al 2013), exceeding the maximum size of ~ 4 kb on other chromosomes (Dumont and Eichler 2013;Trombetta and Cruciani 2017). Nevertheless, the large size of some of the events has been reported (Williams 1998;Repping et al 2006). Although recurrent, only 12 changes in orientation for this inversion have so far been identified here suggests that reconsideration of the possible involvement of double crossovers is merited.…”
Section: A Gene Conversion Mechanism For Most Ttty22-cnv Variationmentioning
confidence: 70%
“…Left: simplified Y-chromosomal phylogeny showing the branching pattern of the lineages considered in this study; branch lengths do not correspond to the number of SNPs. Subsequent columns show the numbers of samples in our data set of 1234 chromosomes with 1, 0, 2, or 3 copies of TTTY22-CNV, the number of deletion (Dels) and duplication (Dups) events inferred from the full phylogeny (total of 20) (Poznik et al 2016), and for comparison, the IR3 orientation reported for these haplogroups, where available (Repping et al 2006). The simplified haplogroups common between the two data sets were named according to the International Society of Genetic Genealogy (2013) Table S3.…”
Section: A Gene Conversion Mechanism For Most Ttty22-cnv Variationmentioning
confidence: 99%
See 2 more Smart Citations